2012
DOI: 10.1061/(asce)co.1943-7862.0000543
|View full text |Cite
|
Sign up to set email alerts
|

Establishing and Weighting Decision Criteria for Building System Selection in Housing Construction

Abstract: Citation: PAN, W., DAINTY, A. and GIBB, A., 2012. Establishing and weighting decision criteria for building system selection in housing construction. Journal of Construction Engineering and AbstractA lack of value-based decision criteria leads to an inability to effectively compare prefabrication and offsite production with conventional construction, which inhibits the realization of benefits of offsite approaches. This paper develops value-based decision criteria and quantifies their relative importance, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(75 citation statements)
references
References 42 publications
0
75
0
Order By: Relevance
“…Khalili et al found that prefabrication configuration and component grouping in production planning for prefabricated structures can reduce total costs by up to 13%, compared to the existing planning approach [31]. Pan et al found that developing and innovating cross-wall technology led to sustained cost savings up to 25% [39]. Meanwhile, integrating design and construction processes [40], supply chain management and learning to fully assure the benefits of off-site technologies were important factors for cost performance [41].…”
Section: Strategy For Cost Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Khalili et al found that prefabrication configuration and component grouping in production planning for prefabricated structures can reduce total costs by up to 13%, compared to the existing planning approach [31]. Pan et al found that developing and innovating cross-wall technology led to sustained cost savings up to 25% [39]. Meanwhile, integrating design and construction processes [40], supply chain management and learning to fully assure the benefits of off-site technologies were important factors for cost performance [41].…”
Section: Strategy For Cost Performancementioning
confidence: 99%
“…Additionally, Chen et al also explored the criteria for selecting the construction method [24]. Pan et al established and weighted decision criteria for building system selection in order to promote sustainable construction [39]. These criteria help stakeholders to select the appropriate construction method between prefabrication or traditional on-site construction.…”
Section: Strategy For Cost Performancementioning
confidence: 99%
“…On-site construction could be a better solution for some cases. Many works have focused on how to evaluate prefabrication and onsite construction (O'Connor, O'Brien, & Choi, 2014) (Pan, Gibb, & Dainty, 2008). What emerges from those studies is that it strongly depends from the considered Country and the boundary conditions.…”
Section: A Is Prefabrication a Viable Strategy?mentioning
confidence: 99%
“…In a wider perspective, economic feasibility and other factors, such as constructability, maintenance convenience and aesthetic quality were also considered using multi-criteria decision-making processes [19,20]. Furthermore, the carbon emission factors (i.e., environmental soundness) when evaluating the suitability of construction methods are also examined [21,22].…”
Section: Identification Of Factors For the Assessment Of Green Technomentioning
confidence: 99%